How familiar are we with decision-making concerning the treatment of perforation after endoscopic mucosal resection (EMR) in the colon? A case report - Tribonias, George; Daferera, Niki; Manola, Margarita-Eleni; Svernlöv, Rikard; Ignatova, Simone; Hjortswang, Henrik (Endoscopy International Open, 2018)
Background and study aims We describe a case of perforation after colonic endoscopic mucosal resection (EMR) that was treated conservatively. We would like to highlight the importance of decision-making mainly based on the endoscopist's point of view in combination with the surgical consultation. Although the radiological imaging is always needed, it cannot solely lead to a decision for operation. Intraperitoneal gas in computed tomography is not always associated with a hole in the endoscopic field and could be possibly explained from a “balloon” phenomenon. The amount of extraluminal air after an EMR does not correlate reciprocally with patient's pain after the procedure. Even though perforation is a radiological diagnosis and endoscopists should be aware of the common post-EMR radiological findings, the surgical examination is mandatory and should be coupled with the endoscopic opinion in order to guide appropriately the treatment in patients with acute pain.